The combined application of Mini-CEX and Check-list Scales in enhancing clinical competence among emergency and critical care residents: a comparative study - Xiao-guang Cao; Xiao-guang Cao; Jia-xin Hu; Huang-chong Jian; Xiong-feng Zhu; Huadong Meng; Min Shao (Frontiers in Medicine)
ObjectivesThis study aims to explore the value of integrating the Mini-Clinical Evaluation Exercise (Mini-CEX) and Check-list Scales in the training of emergency and critical care residents. The study evaluates the effectiveness of these tools in enhancing clinical diagnostic skills, improving teaching outcomes, and optimizing clinical processes.MethodsThis study included 199 emergency and critical care residents who completed their training between January 2018 and April 2024. A paired study design was employed to evaluate the effectiveness of the combined use of the Mini-CEX and Check-list Scales. Initially, all participants used the Mini-CEX to assess their performance during clinical diagnosis and treatment (control group). After training with the Check-list Scales, the same participants underwent a second assessment using the Mini-CEX scale (experimental group). Data were analyzed using various statistical methods, including chi-square tests for categorical data, t-tests for normally distributed data, rank-sum tests for non-normally distributed data, and receiver operating characteristic (ROC) curve analysis to evaluate diagnostic performance.ResultsThe combination of Mini-CEX and Check-list significantly improved clinical competencies across several domains. In the control group, the overall failure rate was 2.513%, the pass rate was 70.352%, and the excellence rate was 27.136%. In contrast, the experimental group showed a reduction in the failure rate to 0%, with a pass rate of 19.598% and an excellence rate of 80.402%. The Mini-CEX scores in the experimental group were significantly higher than those in the control group (p < 0.001), with marked improvements in individual competencies, especially in clinical judgment and overall clinical competence. However, the experimental group had a longer diagnosis and treatment time compared to the control group (66.985 ± 9.126 min vs. 52.387 ± 7.635 min, p < 0.05). Correlation analysis revealed significant associations between various parameters before and after using Check-list tools, indicating improved diagnostic efficiency and clinical skills. The correlation between total score and components such as medical interviewing skills, physical examination skills, and overall clinical competence was notably stronger after the use of the Check-list (p < 0.05). ROC curve analysis demonstrated that all factors had good diagnostic performance, with the lowest being consultation/advice and communication skills [area under curve (AUC) 0.716, 95% CI: 0.680–0.752) and humanistic qualities/professionalism (AUC 0.733, 95% CI: 0.696–0.770), and the highest being clinical judgment (AUC 0.844, 95% CI: 0.813–0.875) and organizational skills/efficiency (AUC 0.815, 95% CI: 0.782–0.848).ConclusionThe integration of the Mini-CEX and Check-list significantly enhances the diagnostic and clinical skills of emergency medicine residents. This combined approach addresses the limitations of traditional training methods and provides an effective model for improving medical education and the quality of care for critically ill patients.